Vegetation diversity and ecological factor assessment via phytoindication on the arena terrace of the Dnipro valley - H. Tutova; K. Panchenko; O. Lisovets; O. Kunakh; O. Zhukov (Regulatory Mechanisms in Biosystems, 2025)
The floodplain terraces of rivers in Europe's temperate zone play a crucial ecological role by supporting unique biodiversity and ensuring landscape stability. This study focused on the vegetation diversity and ecological assessment of the arena terrace, specifically the first above-floodplain terrace of the Dnipro River valley within the Dnipro-Orilsky Nature Reserve. The terrace represents a complex geomorphological feature shaped initially by fluvial processes in the Late Pleistocene and subsequently modified by aeolian activities, resulting in sandy soils and psammophytic vegetation. The research aimed to assess the floristic composition, biodiversity levels, and ecological conditions of plant communities, identifying the primary abiotic factors influe n cing vegetation structure. Geobotanical surveys conducted between 2013 and 2024 documented 297 vascular plant species across 1079 sample plots, classified into 24 associations representing 14 vegetation classes. Results indicated significant variability in vegetation richness and ecological characteristics among different associations. Species richness ranged notably, with the highest diversity observed in meadow and pioneer psammophytic communities, such as Veronic a dillenii-Secaletum sylvestris , while the lowest occurred in communities such as Secaletum sylvestre . Shannon diversity indices confirmed these findings, highlighting meadow associations like Limonio meyeri-Festucetum pseudodalmaticae among the most diverse. The phytoindication method revealed critical abiotic gradients influencing vegetation patterns, primarily moisture, nutrient availability, soil acidity, salt co n tent, carbonate levels, nitrogen content, and soil aeration. The moisture regime showed extensive variability, significantly affec t ing community differentiation. Meadow communities demonstrated high moisture availability, whereas psammophytic commu n ities experienced moisture deficits. Soil nitrogen content sharply contrasted between ecosystems, with meadow and forest ecosy s tems exhibiting significantly higher nitrogen levels compared to psammophytic steppe ecosystems. Climatic regimes, especially thermal and moisture-related indicators, also displayed pronounced variability influencing the ecological niches of plant associ a tions. The thermal radiation balance and continentality indices were relatively stable, whereas ombroclimate and cryoclimate demonstrated significant spatial variation. The study underscored the ecological importance of the first above-floodplain terrace as a biodiversity hotspot, emphasizing its role in maintaining ecosystem stability amid anthropogenic pressures and climate change. Findings offer valuable insights for conservation management, restoration practices, and ecological monitoring, addres s ing a critical gap in understanding floodplain terraces' ecological functions and their responses to environmental gradients.